2023
DOI: 10.3390/ijms24032283
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Response to Nematode Infection

Abstract: Nematode infection is a major threat to the health of humans, domestic animals and wildlife. Nematodes vary in their effect on the host and in the mechanisms underlying immunity but the general features are becoming clear. There is considerable variation among individuals in resistance to infection and much of this variation is due to genetic variation in the immune response. The major histocompatibility complex has a strong influence on resistance to infection but other genes are collectively more important. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 126 publications
(231 reference statements)
0
5
0
Order By: Relevance
“…Columbianum, T. colubriformis, and H. contortus in sheep; A. caninum in dogs; and Trichinella spiralis in pigs, with varying levels of success as summarised in Table 1. Nematodes are large extracellular parasites with complex genomes that are required for escaping various immune responses for successful establishment in the host [37]. An effective vaccine would need to stimulate many different host immune pathways to sufficiently survive subsequent infection.…”
Section: Vaccination As a Parasite Control Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Columbianum, T. colubriformis, and H. contortus in sheep; A. caninum in dogs; and Trichinella spiralis in pigs, with varying levels of success as summarised in Table 1. Nematodes are large extracellular parasites with complex genomes that are required for escaping various immune responses for successful establishment in the host [37]. An effective vaccine would need to stimulate many different host immune pathways to sufficiently survive subsequent infection.…”
Section: Vaccination As a Parasite Control Methodsmentioning
confidence: 99%
“…The development of immune competence primarily occurs through the prevention of the establishment of newly ingested larvae within the gastrointestinal tract, suppression of parasite growth, expulsion of adult worms, or a combination of all three mechanisms [34,35]. Immunity to intestinal worms also develops more rapidly when compared to abomasal worms [36,37]. It has also been shown that immune responses against GINs in small ruminants is different in sheep when compared to goats [38].…”
Section: Immune Responses To Gin Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…grade Necator americanus (hookworm) infection in the rural United States [4], only causes a self-limited colonization with no overt pathology. Helminth infections trigger an immune response in their mammalian hosts but are often able to regulate that response to promote the survival of the parasite and suppress expulsion, although a comprehensive understanding of the mechanism of the latter is lacking [5]. Helminthic regulation or immunity is clearly beneficial for the parasite, but as we will see throughout this review, the induction of immune regulatory pathways can have favorable effects on the host and the host's immune function (Figures 1 and 2).…”
Section: Helminths As Infectious or Commensal Agentsmentioning
confidence: 99%